Review on the Synthesis of Bio-Active Spiro-Fused Heterocyclic Molecules - Patel, Geetika; Patel, Ashok Raj; Kheti, Sameera; Sao, Parimal K.; Rathore, Gargee; Banerjee, Subhash (Current Organocatalysis, 2023)
Background: The spiro entity and heterocyclic scaffolds are decorated with a variety of biological and pharmaceutical properties. Therefore, the fusion of spiro compounds with individual moieties. Thus, the designing and expansion of the methods for the synthesis of various spiro-fused heterocyclic scaffolds are significantly important for synthetic organic chemistry. Methods: A variety of spiro-fused heterocyclic scaffolds are synthesized through different strategies and methods, such as one-pot multi-components synthesis, and multi-step methods via different organic reactions. Results: The wide range of the applications and their interesting biological and medicinal properties encouraged the interest of the researchers to design and construct advanced strategies and methodologies for synthesizing novel spiro-fused heterocyclic molecules which resulted in the publication of numerous research papers and review articles in the literature. In this review article, we have access to the various Schemes for the synthesis of different spiro-fused heterocyclic molecules and their biological importance.
Keywords: bio-active